KAJIAN YURIDIS TERKAIT PENGEMBANGAN IKLIM INVESTASI INDONESIA DI ERA PANDEMI COVID-19 - Lis Julianti (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2021)
Investment is a sector that plays an important role in economic growth in a country. Indonesia is a country that has enormous economic potential to attract investors to invest, but has not been able to create a conducive investment climate. The existence of the COVID-19 pandemic has further exacerbated the decline in investment in Indonesia. This is due to various tight restrictions, the complexity of managing licensing and regulations that still overlap between the center and the regions. The research method used is juridical normative which is based on secondary legal materials. This study uses an approach: statute approach, and conceptual approach. The technique of searching for legal materials uses the document study technique (library research), and the analysis of the study uses qualitative analysis. The results of this study indicate that the Government has made maximum efforts by issuing various regulations or policies in order to revive the investment climate in Indonesia so that the country's economic growth can increase, and is able to guarantee legal certainty in doing business in Indonesia.